Asymmetric price adjustment and loss aversion - Garcia, João Marcos Bastos Vilar (2016)
Asymmetric price adjustment is observed in several markets, most notably gasoline retail: a cost increase is passed through to consumers faster than a cost decrease. I develop a consumer-search model that generates this prediction under loss aversion. A fraction of consumers are ignorant of market prices and can choose to acquire information costly, allowing firms to profit with price dispersion. Asymmetric price adjustment emerges if consumers are loss-averse in relation to a reference price. Higher costs make consumers more willing to search, but also lower the probability of finding low prices, generating convexity in the cost-price relation.